Stakeholders’ feedback integration in spatial planning using Importance Performance Analysis: the case of the Provincial Strategic Plan of the Autonomous Province of Bolzano-South Tyrol (IT) - Ravazzoli, Elisa; Dalla Torre, Cristina; Labadini, Alice; Maino, Federica (Frontiers in Sustainable Cities, 2025)
Importance Performance Analysis (IPA) is a research method employed to comprehend and analyze stakeholder feedback on particular issues. A substantial body of research has demonstrated the efficacy of this methodology as a quantitative approach. To date, there has been a paucity of research using IPA as a methodology for integrating stakeholder feedback into the development of strategic spatial plans. The integration of stakeholder feedback is crucial for the development of inclusive, well-informed, and responsive decision-making processes. The objective of this paper is to contribute to the existing body of knowledge on the utilization of the IPA method in the context of spatial planning. This research presented in this paper employs the Provincial Strategic Plan of the Autonomous Province of Bolzano-Bozen as a case study. In particular, the IPA method was employed to analyze the level of importance and performance of the objectives set out in the Provincial Strategic Plan. Importance refers to the importance of the specific objectives for the future development of the area, while performance refers to how well the specific objectives were formulated. The IPA method has been demonstrated to be an effective assessment instrument. The findings demonstrate that the IPA approach enabled the effective gathering of stakeholders’ feedback in a systematic manner, identifying pivotal issues and potential shortcomings, and providing policy makers with structured recommendations on how to reformulate strategies and plans.